A POETIC CRITIQUE OF SOCIAL BEAUTY STANDARDS AND GENDER ROLES IN MARGE PIERCY’S BARBIE DOLL - Neswari, Birgitta Ardhana (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2025)
This study explores how cultural narratives in poetry reveal and critique societal beauty standards and fixated gender roles. This poem is analyzed using qualitative content analysis, through the lens of myth and symbol theory, psychoanalytic feminism, and gender role theory to uncover deeper meanings behind symbolic representations and internalized expectations in the poem. The figure of the Barbie doll serves as a cultural myth, promoting an idealized femininity that reinforces traditional norms. These ideals, internalized through early socialization and unconscious pressure, shape women’s identities, leading to emotional conflict and self-alienation. Gender roles theory further explains how behaviors, responsibilities, and values are assigned based on socially constructed expectations, often limiting individual potential. The poem demonstrates how these societal forces prioritize appearance over ability, suppressing authenticity and self-worth. Through its critique, the poem remains a powerful commentary on how enduring myths and roles continue to influence women’s lives in contemporary society.Keywords: appearance, Barbie Doll, beauty standard, gender roles, stereotype